Алкилирование 1,2,4-триазола в водно-щелочной среде в присутствии N-метилморфолин N-оксида и некоторые превращения полученных продуктов - Алексанян, А. Г.; Бичахчян, Л. А.; Асратян, А. Г.; Данагулян, Г. Г.; Аттарян, О. С. («Գիտություն» հրատ.)
В работе изучено алкилирование 1,2,4-триазола различными алкилгалогенидами (1,2-дихлорэтан, пропаргилбромид, 1,4-дихлорбут-2-ен) в водно-щелочной среде в системе N-метилморфолин N-оксида/Н2О (NМО), без применения органических растворителей. Найдено, что определяющим фактором при алкилировании 1,2,4-триазола в системе NМО /Н2О с использованием МФК является его основность азола. В той же системе изучено дегидро-хлорирование полученных продуктов. Исследованы трансформации 1-пропаргил-1,2,4-триазола в водно-спиртовых растворах поташа․ Տվյալ աշխատանքում ուսումնասիրվում է 1,2,4–տրիազոլի ալկիլացումը տարμեր հալոգենալկաններով, ինչպիսիքն են 1,2-դիքլորէթանը, պրոպարգիլμրոմիդը և 1,4–դիքլորբութ–2–են–ը, առանց օրգանական լուծիչների կիրառման, ջրահիմնային միջավայրում, N–մեթիլմորֆոլին–N–օքսիդ/ջուր համակարգի առկայությամբ։ Որոշված է, որ 1,2,4–տրիազոլի ալկիլման որոշիչ գործոն է հանդիսանում վերջինիս հիմնայնությունը, որը ալկալու ազդեցությամμ հանգեցնում է դեպրոտոնացման և ՄՖԿ/ՆՄՄՕ համակարգում ալկիլման ռեակցիաներն ընթանում են առանց որևէ բարդության։ Նույն համակարգում ուսումնասիրված է նաև ստացված վերջնանյութերի դեհիդրոքլորացումը։ Ուսումնասիրվել է պոտաշի ջրասպիրտային լուծույթներում 1–պրոպարգիլ-1,2,4–տրիազոլի մոդիֆիկացիան։ In this work, we have studied the alkylation of 1,2,4-triazole with various haloalkanes, such as 1,2-dichloroethane, propargyl bromide, and 1,4-dichlorobut-2-ene, without the use of organic solvents in an aqueous-alkaline medium in the N-methylmorpholine N-oxide/H2O system. It was found that the determining factor in the alkylation of 1,2,4-triazole is its basicity, which leads to deprotonation under the influence of alkali, and the alkylation reactions in the PTC/NMO system proceed without any complications. It was experimentally found that the optimum is the molar ratio of the reagents – triazole: KOH: dichloroethane, in the PTC/NMO/KOH system is 0.1: 0.1: 0.6, which 55-60% yield of 1-(2'-chloroethyl)-1,2,4-triazole. In contrast to 1-(2'-chloroethyl)pyrazoles, the dehydrochlorination of 1-(2'-chloroethyl)-1,2,4-triazole in a 50% aqueous solution of NMO in an alkaline medium proceeds in much milder conditions, at a temperature of 20-25oC, and the yield of 1-vinyl-1,2,4-triazole is 70%. The modification of 1-propargyl-1,2,4-triazole in aqueous-alcoholic solutions of potash has been studied. The modification of the triple bond at the nitrogen atom of the triazole ring proceeds successfully with the formation of 1-(2-methoxyallyl)-1H-1,2,4-triazole and E [1-(2-methoxyprop-1-en-1-yl)]-1H-1,2,4-triazole with a total yield of 75%. When passing from methanol to isopropanol, it was found that the triple bond of 1-propargyl-1,2,4-triazole chemoselectively undergoes prototropic rearrangement with the formation of 1-allenyl-1H-1,2,4-triazole․
Keywords: Органическая химия; Биоорганическая химия